1974
DOI: 10.1021/ja00810a069
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the electrophilic ring opening of cyclopropanes by deuterium(1+) ion. Evidence for an unsymmetrical, nonrotating, corner-protonated cyclopropane

Abstract: It could be argued that opening occurs both from corner-and edge-protonated species, with perhaps the 5 % erythro acetate found in the opening of 1 (the product of nucleophilic retention) arising from the latter intermediate via an open carbonium ion. We think it unlikely that if opening were occurring competitively from both 6 and 8, the stereochemical results would remain constant over such a wide range of solvents and reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On this catalyst, double bonds migrated in a step‐wise manner. Additionally, skeletal isomerization to methyl substituted olefins occurred, presumably through a protonated cyclopropyl intermediate . During skeletal isomerization, the methyl groups formed at nearly random positions along the carbon chain, regardless of the double bond location in the starting olefin, and the catalyst was inactive towards linear alkanes under the conditions of our experiments.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…On this catalyst, double bonds migrated in a step‐wise manner. Additionally, skeletal isomerization to methyl substituted olefins occurred, presumably through a protonated cyclopropyl intermediate . During skeletal isomerization, the methyl groups formed at nearly random positions along the carbon chain, regardless of the double bond location in the starting olefin, and the catalyst was inactive towards linear alkanes under the conditions of our experiments.…”
Section: Resultsmentioning
confidence: 71%
“…We think the intermediates in our previous experiments opened by 1,2 hydride shifts that led always (or almost always) to a tertiary rather than a secondary carbenium ion. The acidic proton associated with such cyclopropyl intermediates appears to protonate either edge‐wise on one of the carbon–carbon bonds or on a corner carbon of the ring and is rapidly mobile. Calculations have indicated that corner‐protonated species are slightly more stable than edge‐protonated species and that proton migration occurs rapidly through the edge‐protonated intermediate .…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] The extra proton is rapidly mobile around the perimeter of the ring, binding alternately at corner carbons and along edges. [ 17–20 ] Each carbon alpha to the ring interacts with both the ring carbons on its opposite side of the ring. When these ring carbons are protonated, they serve as leaving groups, and each alpha carbon can form two new protonated cyclopropanes, as shown in Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…The ring opening of cyclopropanes by electrophiles occurs in the direction of the more stable carbocation with either retention or inversion of configuration at the site of the electrophilic attack, depending on the nature and configuration of the ring substituents, whereas the stereochemistry of the nucleophilic step takes place with complete or strongly predominant inversion of configuration. [1][2][3][4] Recently it has been shown5 that the ring opening of phenylcyclopropane la with mercuric salts occurs, according to expectation,1-2-4•6 by attack of the electrophile on the least-substituted carbon, in the direction of the benzylic carbon. However, the stereochemistry of the nucleophilic step was highly variable, ranging from almost complete inversion to markedly predominant retention of configuration depending on the type of mercuric salt and on the solvent.…”
mentioning
confidence: 99%